PENGELOLAAN PEMBIAYAAN PENDIDIKAN MELALUI BANTUAN OPERASIONAL SEKOLAH PADA MIN CEMPALA KUNENG KABUPATEN PIDIE - Tarmizi .; Jamaluddin Idris; Djailani AR (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: State Government Elementary School Cempala Kuneng is an educational institution that serves as a base level finance management education research and discussion of the results of this study, the management of the financing of education at the Min Cempala Kuneng have been implemented as programmed. This study used a descriptive approach and qualitative methods of data collection techniques documentation, observations and interviews, the research subject chief Madrasah, committee, treasurer, operator / administrative staff and teachers councils in Cempala Kuneng MIN. This study shows that: 1) planning on BOS MIN Cempala Kuneng already accordance with prevailing regulations. implementation is transparent and used in accordance with the existing guidelines, previously held a meeting with the school committee and the board of teachers. 2) Financing on BOS MIN Cempala Kuneng guided by the guide book for the procurement of BOS is the subject of books, teacher training, purchase of consumables, implement student activities, for transport costs, procurement of laboratory supplies, documentation, maintenance costs and the cost of making and lightweight procurement report. 3) Monitoring of the implementation of BOS MIN Cempala Kuneng made superintendent of schools and education authorities who are monitoring the implementation of government's efforts mesikpun indirectly but very helpful in preventing the abuse of authority and misconduct. 4). BOS funds MIN Cempala Kuneng very supportive school students to free tuition, support schools in implementing the program activities, either to improve the infrastructure and improve the competence of teachers and educators.Keywords: Management, Financing, and Supervision.Abstrak: Madrasah Ibtidaiyah Negeri Cempala Kuneng merupakan suatu lembaga pendidikan tingkat dasar yang berperan sebagai Pengelolaan pembiayaan pendidikan Dari hasil penelitian dan pembahasan penelitian ini, maka pengelolaan pembiayaan pendidikan pada Min Cempala Kuneng sudah dilaksanakan sesuai yang diprogramkan. Penelitian ini menggunakan pendekatan deskriptif dan metode kualitatif dengan teknik pengumpulan data dokumentasi, observasi dan wawancara, Subjek penelitian kepala Madrasah, Komite, bendahara, operator/tenaga administrasi dan dewan guru di MIN Cempala Kuneng. Penelitian ini menunjukkan bahwa: 1) perencaan dana BOS pada MIN Cempala Kuneng sudah sesuai ketentuan yang berlaku. pelaksanaannya sudah transparan dan dimanfaatkan sesuai dengan juknis yang ada, sebelumnya diadakan rapat dengan komite sekolah dan dewan guru. 2) Pembiayaan dana BOS pada MIN Cempala Kuneng berpedoman pada buku panduan BOS yaitu untuk pengadaan buku pokok pelajaran, pelatihan guru, membeli bahan habis pakai, melaksanakan kegiatan kesiswaan, untuk biaya transport, pengadaan bahan laboratorium, dokumentasi, biaya perawatan ringan dan biaya pembuatan dan pengadaan laporan. 3) Pengawasan terhadap pelaksanaan dana BOS MIN Cempala Kuneng dilakukan pengawas sekolah dan dinas pendidikan yang merupakan upaya pengawasan penyelenggaraan pemerintah mesikpun secara tidak langsung namun sangat membantu dalam mencegah adanya penyalahgunaan wewenang dan tindakan pelanggaran hukum. 4). Dana BOS MIN Cempala Kuneng sangat mendukung sekolah untuk membebaskan iuran siswa, mendukung program sekolah dalam melaksanakan kegiatannya baik untuk meningkatkan sarana dan prasarana serta meningkatkan kompetensi pendidik dan tenaga kependidikan.Kata kunci : Pengelolaan, Pembiayaan, dan Pengawasan